The Effect of Store Atmosphere on Consumer Purchase Decisions at Kentucky Fried Chicken Serpong Branch Tangerang Selatan - Yahya, Adibah; Haryadi, Rofiq Noorman (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2023)
This study aims to determine the effect of store atmosphere on purchasing decisions at Kentucky Fried Chicken Serpong Branch, South Tangerang. The method used is explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research store atmosphere variable obtained an average score of 3.41 with good criteria. Purchasing decision variable obtained an average score of 3.84 with good criteria. Store atmosphere has a significant effect on purchasing decisions with the regression equation Y = 9.196 + 0.856X, and a correlation value of 0.777 or strong with a determination of 60.4%. The hypothesis test obtained a significance of 0.000 <0.05.